Legal Implications of Examining Notarial Original of the Deed in Corruption Cases: Procedural Analysis and Barriers to Law Enforcement - Wicaksono, Ananda Kukuh; Madjid, Abdul; Widhiyanti, Hanif Nur (CV. AFDIFAL MAJU BERKAH, 2024)
This article aims to analyze the application of Article 36 of Law Number 31 of 1999 concerning the Original of the deed as evidence in corruption criminal cases and the legal implications if investigators fail to obtain permission from the Honorary Council of Notaries to examine the Original of the deed. This study employs a normative juridical research method, using both the statute approach and the conceptual approach. The legal materials consist of primary legal sources, which include Article 66 of Law Number 2 of 2014 amending Law Number 30 of 2004 concerning the Position of Notary and Article 36 of Law Number 31 of 1999 on the Eradication of Corruption Crimes, as well as secondary legal sources, including relevant publications related to the issues raised in this study. These legal materials are analyzed using a perspective analysis, employing grammatical and systematic interpretation methods. The research findings indicate that, based on Article 36 of Law Number 31 of 1999 on the Eradication of Corruption Crimes, which regulates investigations and prosecutions of corruption offenses, there is no legal certainty in its application due to the involvement of the Indonesian Prosecutor's Office and the Honorary Council of Notaries or sectoral ego within each institution. The legal implication of failing to grant investigators permission to examine the Original of the deed of the Honorary Council of Notaries is that it prevents the achievement of perfect proof, as the Original of the deed holds a perfect evidentiary value in proving the alleged corruption crime.